Inovasi Program Perpustakaan Dalam Meningkatkan Literasi Siswa di MTs Ummul Quro Putri Pamekasan - Lailatul Anisa; Ali Nurhadi (Kartika: Jurnal Studi Keislaman, 2026)
The madrasah library plays a strategic role in strengthening students’ literacy culture within the framework of Islamic educational management, which positions literacy as an integral part of intellectual development and religious character building. Less innovative management may weaken its educational function and reduce students’ reading interest. This study aims to analyze the implementation of library program innovations and examine the managerial, cultural, and institutional factors influencing their success in improving students’ literacy at MTs. Ummul Quro Putri Pamekasan. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that innovations were implemented through the development of creative reading corners, daily reading habituation, writing workshops, and active student involvement in literacy activities. The program’s success was supported by responsive school leadership, proactive librarians, teacher collaboration, and a growing religious literacy culture within the school environment. These findings affirm that library innovation depends not only on technical aspects but also on strong institutional management and a supportive school culture